Large area single-element si solar cells based C-PV/T module - Antoschenko, V.S.; Francev, Yu.V.; Lavrischev, O.A.; Antoschenko, Yh.V. (Recent Contributions to Physics, 2012)
A new type of the concentrator photovoltaic module based on the Si solar cell with back contact structure is proposed in the present study. This device works effectively in the region of low radiation concentrations ranging from 8x up to 12x. I-V characteristics of the module for the sun simulator in the range of the radiation concentrations between 1x to 12x and it’s temperature dependence at constant irradiance level (8x) have been measured. Solar cell design is similar to the back-contact structure MWT (Metallization Wrap Throu) [1], in which the current-collecting front tires moved to the back of the element and electrically connected to the grid through the front holes formed over the entire area of the solar cell. The photoelectric characteristics depending on the concentration of light and temperature.
Keywords: solar cells, silicon, concentrator teplofotoelektrichesky module, photovoltaic characteristics